A Conditioning Sciatic Nerve Lesion Triggers a Pro-regenerative State in Primary Sensory Neurons Also of Dorsal Root Ganglia Non-associated With the Damaged Nerve - Dubový, Petr; Klusáková, Ilona; Hradilová-Svíženská, Ivana; Brázda, Václav; Kohoutková, Marcela; Joukal, Marek (Frontiers in Cellular Neuroscience, 2019)
The primary sensory neurons of dorsal root ganglia (DRG) are a very useful model to study the neuronal regenerative program that is a prerequisite for successful axon regeneration after peripheral nerve injury. 7 days after a unilateral sciatic nerve injury by compression or transection, we detected a bilateral increase in GAP-43 and SCG-10 mRNA and protein levels not only in DRG neurons of lumbar spinal cord segments (L4-L5) associated with injured nerve, but also in remote cervical segments (C6-C8). The increase in regeneration-associated proteins in the cervical DRG neurons was associated with the greater length of regenerated axons one day after ulnar nerve crush following prior sciatic nerve injury as compared to controls with only ulnar nerve crush. The increased axonal regeneration capacity of cervical DRG neurons after a prior conditioning sciatic nerve lesion was confirmed by neurite outgrowth assay of in vitro cultivated DRG neurons. Intrathecal injection of IL-6 or a JAK2 inhibitor (AG490) revealed a role for the IL-6 signaling pathway in activating the pro-regenerative state in remote DRG neurons. Our results suggest that the pro-regenerative state induced in the DRG neurons non-associated with the injured nerve reflects a systemic reaction of these neurons to unilateral sciatic nerve injury.